Física básica: Incidencia de la instrucción sobre los errores conceptuales - Salinas de Sandoval, J.; Cudmani, Leonor C. de; Pesa de Danón, M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The incidence of some instructional aspects on the persistency of preconcepts and errors has been analized. Confusions, derived from both, the no -integration of friction forces into the introductory experiencies to the mechanic laws study and the fact of not taking into account quantitative criterions to control the laws and models validity, are particulary studied.